Construction and molecular characterisation of an improved chloroplast transformation vector system as a versatile delivery and expression platform for in-vitro propagated Nicotiana benthamiana - Wang, Eu Sheng (2016)
The objective of this study is to develop a versatile vector system for the delivery and expression of transgenes in the chloroplast genome of N. benthamiana. The successful advent of such a system would vastly streamline the construction process of chloroplast transformation vectors for the expression of recombinant proteins, such as vaccine candidates, in the chloroplasts of N. benthamiana. Transgenes targeted to the chloroplasts of higher plants are expected to be expressed at considerably higher levels as compared to nuclear expression, resulting in more significant accumulation of recombinant proteins. In this study, a 2-part chloroplast transformation vector system was developed and two new GFP vector prototypes, pEXPR-G and pEXPR-UG were generated for preliminary evaluation of functionality. The aadA and GFP expression cassettes of pEXPR-G and pEXPR-UG were evaluated in E. coli prior to actual delivery into N. benthamiana via particle bombardment. Particle bombardment parameters were optimised with particular emphasis on minimising excessive damage to the target tissue in order to facilitate the recovery of antibiotic resistant shoots and calli following transformation. To further evaluate the versatility of the developed system for the expression of vaccine antigens, recombinant vectors, pEXPR-HA and pEXPR-NA were constructed for the delivery of hemagglutinin (HA) and neuraminidase (NA) genes of avian influenza strain H5N1 into the chloroplast genome of N. benthamiana. Experimental results indicated that pEXPR-G and pEXPR-UG were fundamentally functional in E. coli and both the aadA and GFP expression cassettes were active, allowing the bacteria to withstand 500mg/l spectinomycin and express the transgene of interest at the protein level. Similar results were also observed in transplastomic N. benthamiana transformed with pEXPR-UG and pEXPR-NA. In essence, the developed 2-part chloroplast transformation vector system was found to be highly versatile and could be conveniently applied for the construction of transformation vectors for the delivery and expression of HA and NA in the chloroplast of N. benthamiana.